Theoretical and organizational aspects of optimization of activities of trade enterprises based on the logistic approach - Boichyk, Iryna; Spyk, Halyna; Voloshyn, Orysya (Herald of Economics, 2020)
Introduction. Trade enterprises aim to meet consumer demand and, as a result, make a profit. Uncertainty of the external environment and the presence of a number of different problems in the economic activity of trade enterprises necessitates a revision of approaches to the formation of trade and technological processes and their optimization based on the use of modern logistics tools.Purpose. The purpose of the article is to justify the need for the use of logistic tools in organizing trade and technological processes at trade enterprises, to identify the relevant stages of the implementation of logistics, the specificity of the main elements of the trading process.Methods. To establish and identify the constituent elements of trade and technological processes, the study used analytical empiricism with an emphasis on the logistic approach, which allows the formation of effective trading activities based on the optimization of logistic processes. The study used the method of assessment and generalization to develop and substantiate proposals aimed at the development of trading activities on a logistical basis. results. A conceptual approach to the introduction of logistics at trade enterprises has been formed taking into account the possibilities of optimizing the movement of goods based on high-quality information support for goods flows and their material and financial support. The study substantiates that the effective development of a trading company is possible by combining two important components of the process: a set of trading and technological processes, which are a totality of logistic operations for selling goods to customers and management of trade and technological processes. The result of the study is also the authentication of the stages of the formation of the logistics system and the development of the trading company, creating opportunities for the development of subsystems for managing its productivity, including through the use of modern information systems and platforms. Discussion. In this context, perspective direction of further research is the development of methods of analysis of actual indicators, research of components of formation of information support of reengineering of trade and technological processes of trade enterprises with use of modern software products and their resource potential.